Application of Anodization Process for Cast Aluminium Surface Properties Enhancement - Włodarczyk-Fligier A.; Labisz K.; Polok-Rubiniec M.; Konieczny J. (Archives of Metallurgy and Materials, 2016)
An huge interest is observed in last years in metal matrix composite, mostly light metal based, which have found their applications in many industry branches, among others in the aircraft industry, automotive-, and armaments ones, as well as in electrical engineering and electronics, where one of the most important issue is related to the corrosion resistance, especially on the surface layer of the used aluminium alloys. This elaboration presents the influence of ceramic phase on the corrosion resistance, quality of the surface layer its thickness and structure of an anodic layer formed on aluminium alloys. As test materials it was applied the aluminium alloys Al-Si-Cu and Al-Cu-Mg, for which heat treatment processes and corrosion tests were carried out. It was presented herein grindability test results and metallographic examination, as well. Hardness of the treated alloys with those ones subjected to corrosion process were compared.